Putative metabolic pathway of mannitol and sorbitol and in sugarcane - Marino, Celso Luís [UNESP]; Leite, Susi Meire Maximino [UNESP]; Farro, Ana Paula Cazerta [UNESP]; Sassaki, Flávio Tetsuo [UNESP]; Campos, Henrique Luis Veronezi de [UNESP]; Coscrato, Virgínia Elias [UNESP] (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 2003)
Até meados da década de 50 acreditava-se que o boro tinha uma importante função no transporte de açúcares em plantas. Na verdade, o boro depende de açúcares álcoois para serem mobilizados dentro da planta. em alguns organismos os principais açúcares envolvidos neste processo são o sorbitol e o manitol, que formam complexos estáveis com o micronutriente. O objetivo deste estudo foi procurar seqüências no banco de dados SugarCane EST Genome Project (SUCEST) que codificam enzimas participantes na via metabólica destes açúcares através da comparação de enzimas de outros organismos. Dezoito contigs de cana-de-açúcar (Saccharum sp.) apresentaram similaridade com onze seqüências de enzimas que compõem a provável via metabólica de sorbitol e manitol a partir de frutose. Destes contigs, sete apresentaram uma alta similaridade entre as seqüências depositadas no GenBank.

Until the mid 1950s, boron was believed to play an important role in the transport of sugars in plants. However, boron actually depends on sugar alcohols to be taken up by the plant. In some cases, the main sugars involved in this process are sorbitol and mannitol which form stable complexes with boron. In this study, the sequences of the SugarCane EST Genome Project (SUCEST) database were searched for enzymes involved in the metabolism of these sugars by comparing them with enzymes from other organisms. Eighteen contigs from sugarcane (Saccharum sp.) presented high similarity with 11 enzymes involved in the putative biosynthetic pathway of sorbitol and mannitol from fructose in sugarcane. Seven of these contigs had high homology with sequences deposited in GenBank.
Provável via metabólica de manitol e sorbitol em cana-de-açúcar
Keywords: boro; polióis; seqüências alvos expressas (ESTs); açúcares-álcoois; boron; expressed sequence tags (ESTs); polyols; sugar alcohol